A Wireless Sensor Network for Endotracheal Tube Cuff Pressure Monitoring - Cipolletti, Marina Paola (2009)
Endotracheal tubes (ETT) are kept in position using inflatable cuffs. The pressure of the cuff needs to be higher than a minimum value to hold the ETT in place. However, pressures exceeding 20mmHg produce damage of different degrees on the trachea. This paper shows an experimental net- work of wireless and low power nodes for monitor- ing the pressure of ETT cuffs (ETTC). All nodes communicate wirelessly through an RF link with a central station that displays values on a PC and gen- erates alarms if values are beyond the limits pre- scribed by the physician. The system was tested to monitor the condition of several patient ETTC in a coronary intensive care unit of the "Hospital Privado del Sur", in Bahia Blanca, Argentina.